Indonesia has 17.504 island and it's the biggest maritim states in the world. It gives a challege for the government it self because if they don't organized it effectively, there will be bad effects and couses cases. As same as case that happened to Ambalat block, this ocean is claimed as an area from two states. This is the second time Indonesia competes to each other, before that they figth to get sipadan ligitan island, and finaly malaysia got that island. Malaysia claims Ambalat Bl - Dewi Dwi Puspitasari S; Etty Eidman; Luky Adrianto (Buletin Ekonomi Perikanan, 2008)
Indonesia has 17.504 island and it's the biggest maritim states in the world. It gives a challege for the government it self because if they don't organized it effectively, there will be bad effects and couses cases. As same as case that happened to Ambalat block, this ocean is claimed as an area from two states. This is the second time Indonesia competes to each other, before that they figth to get sipadan ligitan island, and finaly malaysia got that island. Malaysia claims Ambalat Block based on 1979 map which published in only one side, by drawing a base line until taking a short out of indonesia area. According to the claim, malaysia gives concession to SHELL which is the 011 company from Holland. Whereas, Indonesia has already given concession to italy and england companies. which is the island country claims that this area is the exclusive economic zone and its also as a continental shelf. Ambalat block which is a sulawesi ocean is assumed having a lot of natural riched things. That's the reasons why of the malayslan claim based on. The most important things here is, both of the Countries have ratified the convention law of the sea (UNCLOS 1982) so, they have to finish the problem based on UNCLOS to. The law Study of Ambalat conflict based on UNCLOS : 1. UNCLOS 1982 article 46, Archipelagic States Arr;hipelagic states means a states consitude wholly by one or more arr;hipelagos and may Include other Island. And Malaysia is not the archilpelagic states. 2. UNCLOS 1982 article 47, archipelagic baselines Malaysia cant use the straight archipelagic baselines because they not the archipelagic states. 3. UNCLOS 1982, article 57 ZEE The exclusive economic zone shall not extend beyond nautical miles the baselines from which the breadth of the territrial sea is measured. Dan the ambalat sea include the Indonesian exclusive economic zone . 4. UNCLOS 1982, article 76, Continental shelf Blok ambalat is the pronglotion of its land of east Kalimantan and that blok comes to 200 nautical miles from the baselines indonesian territorial. 5. UNCLOS 1982, article 77, continental Shelf Indonesia have sovereign rights for the purpose of exsploring natural resources of blok amblat.